Herpes Zoster of the Sacral Region without Motor Dysfunction in a 55-year-Old Female: A Case Report and Literature Review - Alsulaiman OA; Alsaati AA; Alsulaiman F; Aljaafari D; Alabdali M (International Medical Case Reports Journal)
Omer A Alsulaiman,1 Ahmed Abdulaziz Alsaati,2 Feras Alsulaiman,3 Danah Aljaafari,3 Majed Alabdali3 1Department of Dermatology, College of Medicine, Imam Abdulrahman bin Faisal University, Dammam, Saudi Arabia; 2Department of Internal Medicine, Jubail General Hospital, Jubail, Saudi Arabia; 3Department of Neurology, College of Medicine, Imam Abdulrahman bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Omer A Alsulaiman, Department of Dermatology, College of Medicine, Imam Abdulrahman bin Faisal University, Dammam, 34222, Saudi Arabia, Email oasulaiman@iau.edu.saAbstract: Herpes zoster infection, commonly known as shingles, typically involves the thoracic and lumbar dermatomes. Sacral involvement is rare, occurring in only 4– 8% of cases. This report presents a 55-year-old female with herpes zoster affecting the S1 dermatome, manifesting as burning pain and clustered vesicles on her right leg, without motor dysfunction or urinary symptoms. A clinical diagnosis was made based on a characteristic unilateral S1 dermatomal vesicular eruption. Despite the rarity of sacral herpes zoster without motor involvement, the patient responded well to antiviral treatment and neuropathic pain management, with no complications noted in the long-term follow-up. This case highlights the necessity for clinicians to consider sacral herpes zoster in patients with radicular pain to prevent misdiagnosis.Keywords: herpes zoster, sacral dermatome, radiculopathy, shingles, neuropathic pain